2021
DOI: 10.1038/s41598-021-90420-2
|View full text |Cite
|
Sign up to set email alerts
|

Activity in the brain’s valuation and mentalizing networks is associated with propagation of online recommendations

Abstract: Word of mouth recommendations influence a wide range of choices and behaviors. What takes place in the mind of recommendation receivers that determines whether they will be successfully influenced? Prior work suggests that brain systems implicated in assessing the value of stimuli (i.e., subjective valuation) and understanding others’ mental states (i.e., mentalizing) play key roles. The current study used neuroimaging and natural language classifiers to extend these findings in a naturalistic context and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…For instance, such brain regions (e.g., medial prefrontal cortex, precuneus, temporoparietal junction, superior temporal sulcus; Dufour et al., 2013 ; Frith & Frith, 2003 ) are activated when people make decisions about sharing information, compared to other types of decisions, and the extent to which information (e.g., news articles) activates these regions is associated with the likelihood of sharing (Baek et al., 2017 ). Activity in these regions is also positively associated with greater likelihood that online recommendations will propagate (Baek, O'Donnell et al., 2021 ). Furthermore, a neural model of information virality (“value‐based virality”) posits that social considerations contribute to an overall subjective value signal that represents the expected value of sharing a piece of information; this overall value signal is directly associated with population‐level virality (how often information is actually shared in the real world; Scholz et al., 2017 ).…”
Section: Applications To Study Social Phenomenamentioning
confidence: 99%
“…For instance, such brain regions (e.g., medial prefrontal cortex, precuneus, temporoparietal junction, superior temporal sulcus; Dufour et al., 2013 ; Frith & Frith, 2003 ) are activated when people make decisions about sharing information, compared to other types of decisions, and the extent to which information (e.g., news articles) activates these regions is associated with the likelihood of sharing (Baek et al., 2017 ). Activity in these regions is also positively associated with greater likelihood that online recommendations will propagate (Baek, O'Donnell et al., 2021 ). Furthermore, a neural model of information virality (“value‐based virality”) posits that social considerations contribute to an overall subjective value signal that represents the expected value of sharing a piece of information; this overall value signal is directly associated with population‐level virality (how often information is actually shared in the real world; Scholz et al., 2017 ).…”
Section: Applications To Study Social Phenomenamentioning
confidence: 99%
“…The neurological processes underlying the formation or changing of opinions due to social media exposure have been studied from the perspective of the presence and nature of biased content, and the way in which others interact with the information (e.g., likes, comments, retweets, etc.). Prior neuroscience work has specifically studied the effect of social influence on opinion formation and opinion change within the social media environment, where a network of brain regions including the striatum, orbitofrontal cortex, and temporoparietal junction appear to have a critical role in this decision-making process ( Baek et al, 2021 ; Casado-Aranda et al, 2020 ; Cascio et al, 2015 ; Falk & Scholz, 2018 ; Falk et al, 2012 ; Izuma & Adolphs, 2013 ; Kappes et al, 2020 ; Klucharev et al, 2011 ; Li et al, 2019 ; Nakao et al, 2016 ; Sherman et al, 2016 ). Specifically, the neural mechanism of opinion change due to social media use has been shown to integrate brain areas of the valuation, social pain/exclusion, and mentalizing systems that include the ventro-medial prefrontal cortex, striatum, medial prefrontal cortex, dorsomedial prefrontal cortex, temporo-parietal junction, posterior cingulate, medial tegmental gyrus, and anterior cingulate ( Baek et al, 2021 ; Cascio et al, 2015 ; Falk et al, 2012 ; Kappes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the neural mechanism of opinion change due to social media use has been shown to integrate brain areas of the valuation, social pain/exclusion, and mentalizing systems that include the ventro-medial prefrontal cortex, striatum, medial prefrontal cortex, dorsomedial prefrontal cortex, temporo-parietal junction, posterior cingulate, medial tegmental gyrus, and anterior cingulate ( Baek et al, 2021 ; Cascio et al, 2015 ; Falk et al, 2012 ; Kappes et al, 2020 ). Other work has suggested that the popularity of content ( Sherman et al, 2016 ) and the valence of the content plays a significant role in swaying opinion on these platforms ( Baek et al, 2021 ). Due to the opportunity social media affords in rapidly disseminating information throughout the globe, it also creates an interesting glimpse into the complex human decision-making process that impacts our everyday lives ( Schmälzle et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The neurological processes underlying the formation or changing of opinions due to social media exposure have been studied from the perspective of the presence and nature of biased content, and the way in which others interact with the information (e.g, likes, comments, retweets, etc.). Prior neuroscience work has specifically studied the effect of social influence on opinion formation and opinion change within the social media environment, where a network of brain regions including the striatum, orbitofrontal cortex, and temporoparietal junction appear to have a critical role in this decision making process (Cascio et al, 2015; Casado-Aranda et al, 2020; Sherman et al, 2016; Baek et al,2021; Nakao et al, 2016; Falk et al, 2012; Falk & Scholz, 2018; Kappes et al, 2020; Izuma & Adolphs, 2013; Li et al, 2019; Klucharev et al, 2011). Specifically, the neural mechanism of opinion change due to social media use has been shown to integrate brain areas of the valuation, social pain/exclusion, and mentalizing systems which include the ventro-medial prefrontal cortex (VMPFC), striatum, medial prefrontal cortex (mPFC), dorsomedial prefrontal cortex (DMPFC), temporo-parietal junction (TPJ), posterior cingulate (PCC), medial tegmental gyrus (MTG), and anterior cingulate (ACC) (Cascio et al, 2015; Baek et al,2021; Kappes et al, 2020; Falk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the neural mechanism of opinion change due to social media use has been shown to integrate brain areas of the valuation, social pain/exclusion, and mentalizing systems which include the ventro-medial prefrontal cortex (VMPFC), striatum, medial prefrontal cortex (mPFC), dorsomedial prefrontal cortex (DMPFC), temporo-parietal junction (TPJ), posterior cingulate (PCC), medial tegmental gyrus (MTG), and anterior cingulate (ACC) (Cascio et al, 2015;Baek et al,2021;Kappes et al, 2020;Falk et al, 2012). Other work has suggested that the popularity of content (Sherman et al, 2016) and the valence of the content plays a significant role in swaying opinion on these platforms (Baek et al, 2021). Due to the opportunity social media affords in rapidly disseminating information throughout the globe, it also creates an interesting glimpse into the complex human decision making process that impacts our everyday lives (Schmälzle et.…”
Section: Introductionmentioning
confidence: 99%